Improving The Tenth Grade Students’ Reading Comprehension Achievement By Using Porpe (Predict, Organize, Rehearse, Practice, And Evaluate) Strategy - Wardatun Najwa (Fakultas Keguruan Dan Ilmu Pendidikan, 2019)
This classroom action research was intended to improve the X-A grade students’ reading comprehension achievement by using PORPE strategy. It was conducted to 25 students of X-A class at SMAI 04 Ma’arif Perintis Tempurejo. Based on the interview with the English teacher, the strategy used by the teacher is not enough to improve the students’ reading comprehension. Besides, the students’ previous score showed that only 4 out of 25 students who achieved the standard minimum score. Therefore, PORPE strategy was chosen to improve the students’ reading comprehension achievement and students’ active participation. PORPE is one of learning strategies that can help students remember significantly more concepts to recall or recognize some information they get from the text. PORPE strategy consists of five steps; Predict, Organize, Rehearse, Practice, and Evaluate.
Reupload Repositori File 18 Mei 2026_Kholif Basri Validasi file repositori 11 Juni 2026_Dea_Firli
Keywords: Students’ Reading